Energy conservation at high power consuming holding furnace with modified coil design and electrical circuits - D. Karthikeyan; V. P. Arumbu; P. Divya; K. Vijayakumar; K. Mani Rahulan (Institute of Advanced Engineering and Science, 2021)
This paper deals with high energy consuming induction holding furnace. The improved version of coil design along with additional electrical interlocks and alarm, modified hydraulic controls, strengthening mechanical structures and energy saving proposals at holding furnace fume extraction system ensures trouble free operation of furnace and hence continuity of production at all the planned plant operational days. This project involves in purchasing of D-section copper extruded coil from Europe–Switzerland for its extended length from existing 3 meters long to 9 Meters which enables in reduction of coil joints. The performance of the holding furnace has improved in terms ofits energy consumption per ton of liquid metal. The payback period for the estimated investment will be less than 2 years.